Effect of calcium dobesilate on macular microvasculature in patients with diabetic retinopathy - Jung-Tae Kim; Ka-Hyun Lee; Min-Woo Lee (PLoS ONE, 2025)
Purpose To investigate the impact of calcium dobesilate (CaD) on the macular microvasculature in patients with diabetic retinopathy (DR) using optical coherence tomography angiography. Methods In this retrospective study, patients with DR were divided into two groups: those treated with 1 g/day of CaD (Group 1) and those without CaD treatment (Group 2). Following the baseline, patients underwent two additional examinations at 3-month intervals for analysis. The vessel density of the superficial vascular complex (SVD) and deep vascular complex (DVD) were compared against prior assessments. Generalized linear mixed models analyzed factors associated with changes in SVD and DVD over time. Results A total of 81 eyes were included: 39 in Group 1 and 42 in Group 2. The mean SVD was 21.8 ± 5.7% at baseline, 23.5 ± 6.5% at 3 months, and 23.3 ± 6.1% at 6 months in Group 1, respectively (P = 0.034), with significant changes observed from baseline to 3 months (P = 0.021), but not from 3 to 6 months (P = 0.745). The mean DVD was 18.2 ± 3.4% at baseline, 20.0 ± 3.9% at 3 months, and 19.9 ± 4.1% at 6 months in Group 1, respectively (P = 0.008), showing a significant increase from baseline to 3 months (P = 0.007), but not from 3 to 6 months (P = 0.825). Group 2 showed no significant changes over time in either SVD (P = 0.175) or DVD (P = 0.156). In Group 1, multivariate analysis identified DR severity as significantly associated with changes in SVD (estimate = 5.07, P = 0.016). Conclusions The administration of CaD positively influences macular microcirculation in DR patients, demonstrating its effectiveness even in advanced stages of the disease.